Advanced Trauma Care for Nurses (ATCN): A Single-Center Analysis of Trauma Nurses Knowledge Gaps. Issue 4 (July 2021) - Kaur, Shivpreet; Rattan, Amulya; Kumar, Hemant; Rao, Shalinee; Kant, Ravi; Misra, Mahesh C.
Abstract : Background: Trauma is a global cause of death and disability, and trauma systems are not well developed in low- and middle-income countries. Training of nurses in trauma care is of utmost importance to improve the organization and delivery of trauma care. Objective: This study aimed to identify common knowledge gaps and develop study aids to improve nurses' performance taking the Advanced Trauma Care for Nurses (ATCN) course. Methods: This is a descriptive, single-center study of the multiple-choice final examinations of the ATCN course conducted over 1 year in the All India Institute of Medical Sciences, Rishikesh, Level I trauma center. The questions missed by candidates were compiled, and the wrong options were tabulated. The most commonly missed questions were identified, and the most commonly marked wrong option was analyzed vis-a-vis the correct answer. Each error was classified into either a theoretical error or a practice-based error. Results: Ninety-six nurses attended 6 courses from June 2019 to June 2020. Of the theoretical-based questions, the top 3 categories of most missed questions were geriatric trauma ( n = 13; 81.2%), massive transfusion ( n = 35; 72.9%), and traumatic brain injury ( n = 35; 72.9%). Of the practice-based questions, the top 3 categories of most missed questions were dislocated extremity management ( n = 54; 79.4%), basic airway ( n = 31; 64.5%), and shock management ( n = 30; 62.5%). Conclusions: Periodic identification and categorization of the ATCN course examination's most frequent knowledge gaps allow instructors to develop teaching aids to enhance instructor teaching and improve trauma nurses' knowledge. Abstract : Supplemental Digital Content is Available in the Text.